2004
DOI: 10.1109/tmag.2003.821560
|View full text |Cite
|
Sign up to set email alerts
|

New Approach for the Prediction of the Electric Field Distribution in Multimode Microwave-Heating Applicators With Mode Stirrers

Abstract: Abstract-We present a new approach for inferring the electric field distribution inside materials in multimode cavities with mode stirrers. We calculate the electric field in the dielectric material by a two-dimensional modeling of a typical multimode microwave applicator with some mobile metallic sheets. We compare simulated results with classical approaches, such as Lambert's law or a constant electric field distribution. The proposed method allows for a better understanding of how these structures can be ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 17 publications
(11 reference statements)
3
52
0
Order By: Relevance
“…1 shows the comparison of present simulation results, experimental results, and simulation results of Plaza-González et al. 4 It can be seen from Fig. 1 that the present simulation results are in better agreement with the experimental results than the previous simulation results.…”
Section: Validation Of Comsol Resultsmentioning
confidence: 49%
See 3 more Smart Citations
“…1 shows the comparison of present simulation results, experimental results, and simulation results of Plaza-González et al. 4 It can be seen from Fig. 1 that the present simulation results are in better agreement with the experimental results than the previous simulation results.…”
Section: Validation Of Comsol Resultsmentioning
confidence: 49%
“…4 It was found that there is a qualitative agreement between the two results i.e. the temperature profile results of simulation and experiments follow similar trend even though there is a slight deviation between the results.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…the heated object is placed in a microwave oven) is more close to practical applications. Besides, Plaza-Gonzalez, et al, [86] studied the case of mode stirrers which are widely used by industrial applicators.…”
Section: Txy Zt T Xy Zmentioning
confidence: 99%